Consumer’s Impulse Buying Behavior: Do Visual Merchandising, Store Atmosphere, Availability of Money, and Promotional Activity Affect it? - Evelyn Wijaya; Onny Setyawan (Bina Nusantara University, 2020)
The research aimed to analyze the influence of visual merchandising, store atmosphere, availability of money,and promotional activity on impulse buying behavior in MINISO Pekanbaru. The research applied a quantitativemethod, and the population was consumers who purchased any product in MINISO Pekanbaru. The sampleamounted to 150 respondents with an accidental sampling technique. The instrument used was a questionnaire byasking questions to respondents. Analysis was conducted by using a multiple regression linear approach with IBMSPSS 23. The results show that the store atmosphere does not significantly influence impulse buying behavior.Meanwhile, visual merchandising, availability of money, and promotional activity significantly affect the impulsebuying behavior. The results imply that MINISO Pekanbaru has implemented a proper marketing strategy to attractconsumers to buy impulsively. However, MINISO Pekanbaru needs to re-consider the display and informationplacement about the products so that the consumers feel comfortable and content to spend a longer time there.